Balance weight composition
The active energy ray curing balance weight composition, featuring a binder resin, inorganic filler, and photopolymerization initiator, addresses the challenge of deep curability in thick coatings, ensuring high productivity and precise weight adjustment for small and precise rotors.
Patent Information
- Application Number
- JP2023155488
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-04-03
AI Technical Summary
Existing balance weight compositions face challenges in achieving deep curability when thick coatings are applied, particularly for smaller and more precise rotors, where high productivity and precise weight adjustment are required.
A composition for active energy ray curing balance weights, comprising a binder resin with polymerizable functional groups, an inorganic filler with a specific gravity of 2.0 or more, and a photopolymerization initiator, which allows for deep curability and high specific gravity, enabling effective use in liquid form and thick coatings.
The composition achieves excellent deep curability and high specific gravity, making it suitable for small and precise rotors, while maintaining high productivity and precise weight adjustment capabilities.
Smart Images

Figure 2025047160000001 
Figure 2025047160000002 
Figure 2025047160000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition for balance weights which is cured by active energy rays such as ultraviolet rays. [Background technology]
[0002] Balance weights are often attached to rotating bodies such as automobile tires and motor impellers. The purpose of this is to adjust the weight uniformity and balance to enable stable rotation without wobble. Initially, the method used was to cast an alloy mainly made of heavy metals such as tungsten and molybdenum, and then machine the weights from the block.
[0003] However, this method has problems such as high costs due to cutting processes and material loss, and difficulty in stabilizing weight accuracy. Therefore, as a manufacturing method for balance weights with excellent productivity and excellent weight accuracy and shape reproducibility, for example, a method of injection molding using a composition consisting of a heavy metal with an average particle size of 1 to 30 μm and a specific gravity of 19 or more and a thermoplastic resin has been proposed (Patent Document 1). Furthermore, as a balance weight with excellent workability, a balance weight in which tungsten with a specified specific gravity and particle size is mixed with a one-liquid adhesive and hardened has been proposed (Patent Document 2).
[0004] Although these improvements have improved workability and precision, in recent years balance weights have become necessary for rotating objects that are much smaller and more precise than in conventional fields, such as small motors such as polygon mirror motors. In this case, there was a demand for UV-curable balance weights that are easy to adjust the specific gravity even when used in small amounts and can cure quickly with high productivity, but there was a problem that it was difficult to cure deep in thick coatings. Therefore, there was a demand for UV-curable balance weights that can be applied in liquid form and have excellent deep curing properties. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Publication No. 7-33905 [Patent Document 2] Patent Publication No. 2004-36675 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide an active energy ray-curable balance weight composition which can be applied in a liquid state and has excellent deep curing properties. [Means for solving the problem]
[0007] In order to solve the above problems, the invention of claim 1 provides an active energy ray-curable composition for balance weights, which comprises a binder resin (A) having a polymerizable functional group, an inorganic filler (B), and a photopolymerization initiator (C), and is characterized in that the specific gravity of the cured composition is 2.0 or more, and the total light transmittance of the cured composition applied to a thickness of 50 μm on a PET substrate having a thickness of 50 μm is 45% or more.
[0008] The invention of claim 2 provides the active energy ray-curable composition for balance weights according to claim 1, characterized in that it contains the inorganic filler (B) having an average particle size of 0.05 to 20 μm.
[0009] The invention of claim 3 provides the active energy ray-curable composition for balance weights according to claim 1, characterized in that (C) contains an α-hydroxyacetophenone type (c1) and an acylphosphine oxide type (c2).
[0010] The invention of claim 4 provides the active energy ray-curable composition for balance weights according to any one of claims 1 to 3, further comprising a dispersant (D). Effect of the Invention
[0011] The composition of the present invention can be applied in a liquid state, is cured by active energy rays such as ultraviolet rays, and has excellent deep curing properties, and is therefore useful as a composition for balance weights. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The composition for balance weights of the present invention is composed of a binder resin (A) having a polymerizable functional group, an inorganic filler (B), and a photopolymerization initiator (C). In this specification, (meth)acrylate includes both acrylate and methacrylate.
[0013] The binder resin (A) having a polymerizable functional group used in the present invention disperses the inorganic filler (B) and is the main component constituting the balance weight. There is no particular limitation on the (A) used, and examples thereof include radical polymerization acrylic resin binders and cationic polymerization epoxy resin binders. Among these, acrylic resin binders are preferred in terms of curing speed. Examples of oligomers of acrylic resin binders include urethane (meth)acrylate (hereinafter referred to as ureac), epoxy (meth)acrylate, polyester (meth)acrylate, polycarbonate (meth)acrylate, acrylic (meth)acrylate, diene (meth)acrylate, etc., which can be used alone or in combination of two or more types.
[0014] A low molecular weight binder may be used as a component other than the oligomer. For example, (meth)acrylates having functional groups such as aliphatic, alicyclic, polyether skeleton, hydroxyl group, and amino group, and acrylamide compounds can be mentioned, and they can be used alone or in combination of two or more. The number of functional groups is preferably multifunctional in terms of reactivity. For example, bifunctional compounds include ethylene glycol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, 1.4-butanediol di(meth)acrylate, and 1.6-hexanediol di(meth)acrylate. Furthermore, trifunctional compounds or higher include pentaerythritol triacrylate, trimethylolpropane triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, and dipentaerythritol hexaacrylate.
[0015] The amount of (A) to be blended depends largely on the specific gravity of (B), and is an amount that results in a specific gravity of the cured composition of 2.0 or more. For example, when the specific gravity of (B) is about 4.0, the amount is 10 to 30% by weight.
[0016] The inorganic filler (B) used in the present invention is blended for the purpose of increasing the specific gravity of the cured product. The specific gravity of (B) is preferably 2.1 or more, more preferably 3.0 or more, and particularly preferably 4.0 or more. The average particle size is preferably 0.05 to 20 μm, more preferably 0.1 to 15 μm, and particularly preferably 0.5 to 10 μm. By keeping it within these ranges, it is easy to adjust the specific gravity of the cured product to 2.0 or more. The average particle size is measured by laser diffraction method (d 50 )
[0017] Examples of (B) having a specific gravity of 2.3 or more include aluminum oxide (specific gravity 2.4), glass (2.4), talc (2.6), calcium carbonate (2.7), barium sulfate (4.3), titanium oxide (4.9), ferric oxide (5.1), zinc oxide (5.5), copper oxide (5.9), tungsten (19.3), gold (19.3), platinum (21.4), etc., and these can be used alone or in combination of two or more types.
[0018] The amount of (B) depends greatly on the total light transmittance of the composition, and is an amount that provides a total light transmittance of 45% or more for the cured composition applied to a thickness of 50 μm on a PET substrate having a thickness of 50 μm, and at the same time provides a specific gravity of 2.0 or more for the cured composition. For example, when the specific gravity of (B) is about 4.0, the amount is 65 to 85% by weight.
[0019] The photopolymerization initiator (C) used in the present invention generates radicals when irradiated with ultraviolet light or an electron beam, and the radicals trigger the polymerization reaction, and general-purpose photopolymerization initiators such as benzyl ketal, acetophenone, and phosphine oxide photopolymerization initiators can be used. By arbitrarily selecting the light absorption wavelength of the polymerization initiator, it is possible to impart curability over a wide wavelength range from the ultraviolet region to the visible light region. Specifically, benzyl ketals include 2,2-dimethoxy-1,2-diphenylethan-1-one, α-hydroxyacetophenones include 1-hydroxy-cyclohexyl-phenyl-ketone and 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, α-aminoacetophenones include 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, and acylphosphine oxides include 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, which may be used alone or in combination of two or more.
[0020] Among these, it is preferable to use α-hydroxyacetophenone type (c1), which is resistant to yellowing, and acylphosphine oxide type (c2), which has excellent internal curing properties. (c1) is particularly preferable because it generates radicals even in the visible light range, which is not excited by the benzophenone structure. In addition, when thickening the cured film to 100 μm or more, it is effective to use (c1) and (c2) in combination.
[0021] The amount of (C) to be blended per 100 parts by weight of component (A) is preferably 3 to 25 parts by weight, more preferably 5 to 20 parts by weight. By using 3 parts by weight or more, sufficient curability can be ensured, and by using 25 parts by weight or less, an excessive amount is not added, and sufficient molecular weight can be ensured even after curing. When (c1) and (c2) are used in combination, the amount of the latter is preferably 0.1 to 0.8 parts per part of the former. Commercially available products of (c1) include Omnirad 184 and 2959, and of (c2) include Omnirad TPO H and 819 (trade names: manufactured by IGM Resins).
[0022] The composition of the present invention preferably contains a dispersant (D) for the purpose of improving the dispersion stability of (B) and adjusting the viscosity to a level suitable for workability. Examples of (D) include polymer dispersants with a molecular weight of 2,000 to 1,000,000, low molecular dispersants with a molecular weight of less than 2,000, and inorganic dispersants. Among these, polymer dispersants that have a high dispersing effect even in small amounts and can be expected to have a repulsion effect due to steric hindrance are preferred. Examples include polyethyleneimine-based, alkylamine-based, polyallylamine-based, polyacrylic acid ester-based, sorbitan aliphatic ester-based, and phosphoric acid-based.
[0023] The amount of (D) is preferably 0.5 to 5% by weight, more preferably 0.8 to 3% by weight, and particularly preferably 1.0 to 2% by weight, based on the total solid content of the composition. By adjusting the amount within this range, it is expected that the stability of the dispersion state, low viscosity, and improved storage stability can be achieved. Commercially available products include DISPERBYK-111 (product name: manufactured by BYK, phosphate polyester type).
[0024] The composition of the present invention may contain various additives, such as a leveling agent, a plasticizer, a tackifier, a defoamer, a thickener, and a wettability adjuster, if necessary, to the extent that the performance is not impaired.
[0025] The solid content of the composition is preferably 80% by weight or more, more preferably 95% by weight or more, and particularly preferably 99% by weight or more, which is substantially solvent-free. If the solid content is 80% by weight or more, thick coating is possible by sufficiently volatilizing the solvent before photocuring.
[0026] The viscosity of the composition at 25° C. is preferably 100 to 100,000 mPa·s, and more preferably 500 to 50,000 mPa·s. By keeping the viscosity within this range, good coating workability can be ensured.
[0027] The specific gravity of the cured product of the composition is 2.0 or more, preferably 2.2 or more, more preferably 2.4 or more, and particularly preferably 2.6 or more. By making it 2.0 or more, it can be used as a good balancer coating material for micro components.
[0028] The total light transmittance of the composition cured product obtained by applying the composition to a thickness of 50 μm on a PET substrate having a thickness of 50 μm is 45% or more, preferably 50% or more, and more preferably 60% or more. If it is less than 45%, when applied in a thick film, the light may not reach deep inside, resulting in insufficient curing. The total light transmittance is largely affected by the type, shape, average particle size, and amount of inorganic filler to be blended. For example, when the filler itself has a relatively high light transmittance and a refractive index close to that of resin, such as glass, the total light transmittance of the resin composition tends to be high. Conversely, when a filler has a very low light transmittance and is easily absorbed by light, such as tungsten, the total light transmittance of the resin composition tends to be low even when added in small amounts.
[0029] The present invention will be described in more detail below with reference to examples and comparative examples, but these are illustrative and are not intended to be limiting. Unless otherwise specified, measurements were performed under conditions of room temperature of 25°C and relative humidity of 65%. The amounts of the ingredients are expressed in parts by weight. EXAMPLES
[0030] Example 1 In a light-shielding bottle, (A) MIRMAER M200 (trade name: manufactured by MIWON, 1.6-hexanediol diacrylate), (B) P-30 (trade name: manufactured by Takehara Chemical Industry Co., Ltd., barium sulfate particle size 1.0 μm, specific gravity 4.3), (c1) Omnirad184 (trade name: manufactured by iGM, α-hydroxyacetophenone type), (c2) Omnirad TPO H(G) (trade name: manufactured by iGM, acylphosphine oxide type), and (D) DISPERBYK-111 (trade name: manufactured by BYK, phosphoric acid polyester type) were placed in the amounts shown in Table 1, and the mixture was stirred for 15 minutes or more using a stirring defoamer until it became uniform, thereby preparing the resin composition of Example 1.
[0031] Examples 2 to 13 and Comparative Examples 1 to 2 In addition to the materials used in Example 1, (A) was MIRMAER M300 (trade name: manufactured by MIWON Co., Ltd., trimethylolpropane triacrylate), as (B), W-6 (trade name: Takehara Chemical Industry Co., Ltd., barium sulfate, particle size 4.5 μm, specific gravity 4.3) and HC-A (trade name: Takehara Chemical Industry Co., Ltd., barium sulfate, particle size 0.1 μm, specific gravity 4.3) and calcium bicarbonate (Maruo Calcium Co., Ltd., particle size 12 μm, specific gravity 2.7) and CB-P15 (trade name: RESONAC Co., Ltd., alumina beads, particle size 16 μm, specific gravity 4.0 by Coulter counter method) and CF0093-05C (trade name: Takara Standard Co., Ltd., glass filler, particle size 15 μm, specific gravity 2.4) and CF0019-10C (trade name: Takara Standard Co., Ltd., glass filler, particle size 15 μm, specific gravity 3.5) and W-4KD (trade name: Japan New Metals Co., Ltd., tungsten, particle size 3 μm, Sub Sieve The resin compositions of Examples 2 to 13 and Comparative Examples 1 and 2 were prepared by adding the amounts shown in Tables 1 and 2 (specific gravity 19.3, determined by the average particle size measured by a sizer) and stirring for 15 minutes or more until homogenous using a stirring and defoaming machine.
[0032] Table 1 JPEG2025047160000001.jpg121155
[0033] Table 2 JPEG2025047160000002.jpg125144
[0034] The evaluation method was as follows.
[0035] Viscosity: Measurements were taken using a Toki Sangyo RE-215R cone-plate viscometer with a rotor with a cone angle of 3°R14 at 25±1°C and 1 rpm. Values between 500 and 10,000 were rated as ◎, values between 100 and less than 500 mPa·s and between 10,000 and 100,000 mPa·s were rated as 〇, and values outside these ranges were rated as ×.
[0036] Total light transmittance: The composition was applied onto a PET film U403 (product name: manufactured by Toray Industries, Inc., thickness 50 μm) so that the thickness after curing was 50 μm, and an electrodeless UV irradiation device F300S / LC-6B manufactured by Fusion UV Systems Japan was used, with an output of 100 mW / cm using a D bulb. 2 , cumulative light intensity 1000mJ / cm 2 The haze was measured in accordance with JIS K7361-1 using a haze meter Haze-GARD2 manufactured by Toyo Seiki Seisakusho Co., Ltd. The evaluation was made as follows: 45% or more was rated as good, and less than 45% was rated as bad.
[0037] Deep curing: A 2 mm thick silicon spacer is placed on a release PET film, and 2 mm of resin is applied. Then, UV irradiation is performed from the same side (using the above-mentioned electrodeless UV irradiation device, output 100 mW / cm with a D bulb). 2 , cumulative light intensity 2000mJ / cm 2 ) and cured. The cured product was then removed and the film thickness of the cured product was measured. If the back side of the irradiated surface was not completely cured, the uncured resin was washed off with isopropyl alcohol before the film thickness of the cured product was measured. Over 1 mm was rated as ◎, 0.5 to 1 mm as ◯, and less than 0.5 mm as ×.
[0038] Specific gravity of cured product: Measured using a metal pycnometer (specific gravity bottle) of known volume in accordance with JIS K 7112B. Evaluation was made as follows: over 2.2: ⊚, 2.0 to 2.2: ◯, and less than 2.0: ×.
[0039] Adhesion: The composition was applied to a 2 mm thick ABS plate with a diameter of 2 mm and a thickness of 0.5 mm, and then irradiated with UV (using the above-mentioned electrodeless UV irradiation device, with an output of 100 mW / cm using a D bulb). 2 , cumulative light intensity 1000mJ / cm 2 ), and then the presence or absence of peeling was evaluated by applying pressure with a finger. If no peeling occurred, it was marked with ◯, and if peeling occurred, it was marked with ×.
[0040] The evaluation results of the examples are shown in Table 3. Table 3 JPEG2025047160000003.jpg78135
[0041] The evaluation results of the comparative examples are shown in Table 4. Table 4 JPEG2025047160000004.jpg86132
[0042] The resin compositions of the examples were excellent in the evaluation of viscosity, total light transmittance, deep curability, specific gravity of the cured product, and adhesion.
[0043] On the other hand, Comparative Example 1 had a low specific gravity of the cured product, and Comparative Example 2 had a low total light transmittance and low deep curing properties, and neither of these were suitable for the present invention.
Claims
1. An active energy ray-curable composition for balance weights, comprising a binder resin (A) having a polymerizable functional group, an inorganic filler (B), and a photopolymerization initiator (C), the specific gravity of the cured composition being 2.0 or more, and the total light transmittance of the cured composition applied to a thickness of 50 μm on a PET substrate having a thickness of 50 μm being 45% or more.
2. 2. The active energy ray-curable composition for balance weights according to claim 1, further comprising (B) an inorganic filler having an average particle size of 0.05 to 20 μm.
3. 2. The active energy ray-curable composition for balance weights according to claim 1, wherein the (C) contains an α-hydroxyacetophenone type (c1) and an acylphosphine oxide type (c2).
4. 4. The active energy ray-curable composition for balance weights according to claim 1, further comprising a dispersant (D).
Citation Information
Patent Citations
Composition for balancing weight of instrument pointer
JP1995033905A
Balance weight
JP2004036675A